Schwann cell-derived Apolipoprotein D controls the dynamics of post-injury myelin recognition and degradation - García-Mateo, Nadia; Ganfornina, Maria D.; Montero, Olimpio; Gijón, Miguel A.; Murphy, Robert C.; Sanchez, Diego (Frontiers in Cellular Neuroscience, 2014)
Management of lipids, particularly signaling lipids that control neuroinflammation, is crucial for the regeneration capability of a damaged nervous system. Knowledge of pro- and anti-inflammatory signals after nervous system injury is extensive, most of them being proteins acting through well-known receptors and intracellular cascades. However, the role of lipid binding extracellular proteins able to modify the fate of lipids released after injury is not well understood. Apolipoprotein D (ApoD) is an extracellular lipid binding protein of the Lipocalin family induced upon nervous system injury. Our previous study shows that axon regeneration is delayed without ApoD, and suggests its participation in early events during Wallerian degeneration. Here we demonstrate that ApoD is expressed by myelinating and non-myelinating Schwann cells and is induced early upon nerve injury. We show that ApoD, known to bind arachidonic acid (AA), also interacts with lysophosphatidylcholine (LPC) in vitro. We use an in vivo model of nerve crush injury, a nerve explant injury model, and cultured macrophages exposed to purified myelin, to uncover that: (i) ApoD regulates denervated Schwann cell-macrophage signaling, dampening MCP1- and Tnf-dependent macrophage recruitment and activation upon injury; (ii) ApoD controls the over-expression of the phagocytosis activator Galectin-3 by infiltrated macrophages; (iii) ApoD controls the basal and injury-triggered levels of LPC and AA; (iv) ApoD modifies the dynamics of myelin-macrophage interaction, favoring the initiation of phagocytosis and promoting myelin degradation. Regulation of macrophage behaviour by Schwann-derived ApoD is therefore a key mechanism conditioning nerve injury resolution. These results place ApoD as a lipid binding protein controlling the signals exchanged between glia, neurons and blood-borne cells during nerve recovery after injury, and open the possibility for a therapeutic use of ApoD as a regeneration-promoting agent.